Patient-reported outcomes and home-based self-swabs for influenza-like illness events - lessons learned from the 2023/2024 DANFLU-2 Homeswab PRO substudy - Filip Soeskov Davidovski; Kristoffer Grundtvig Skaarup; Niklas Dyrby Johansen; Daniel Modin; Nabila Shaikh; Jose Bartelt-Hofer; Matthew M. Loiacono; Rebecca C. Harris; Carsten Schade Larsen; Lykke Larsen; Lothar Wiese; Michael Dalager-Pedersen; et al. (Journal of Patient-Reported Outcomes)
Abstract Background Self-swabs and digital patient-reported outcomes (PROs) offer innovative tools for decentralized monitoring of infectious diseases. The DANFLU-2 HomeSwab PRO substudy evaluated the feasibility of using these methods for tracking influenza-like illness (ILI) within a large-scale, pragmatic, randomized trial. Methods During the 2023/2024 influenza season, adults aged ≥ 65 years were recruited from the DANFLU-2 trial, which evaluates the relative effectiveness of high-dose influenza vaccine compared to standard-dose. Participants were instructed to self-swab at home upon ILI symptom onset and complete the Respiratory Infection Intensity and Impact Questionnaire (RiiQ™) for 14 days. Swabs were registered via QR code in a webapp and mailed for centralized PCR testing. Compliance was defined as completing all 14 days of RiiQ™ reporting. Results Among 1,976 enrolled participants, 208 (10.5%) completed at least one RiiQ™, and 171 (82.2%) met the ILI case definition. Most participants found self-swabbing easy (66.1%) and more practical than visiting a clinic (78.6%). Compliance with daily RiiQ™ symptom tracking was 85.7%. Among those with ILI, 89.4% performed a self-swab within 1 day [IQR: 0; 3] of symptom onset; 65.8% of swabs were correctly registered in the webapp, and 96.5% were RNaseP-positive. Thirty-six participants (1.8%) withdrew, mainly due to weekly reminders; allowing reduced reminder frequency improved retention. Conclusion The study confirmed the feasibility of using home-based self-swabs for remote disease diagnosis and digital PRO tracking for symptoms during ILI events in a large-scale, pragmatic randomized trial. While the approach proved viable, the findings also highlighted areas for improvement in participant engagement and data collection efficiency. Clinicaltrials.gov ID NCT05517174.